ChemInform Abstract: Practical Large‐Scale Preparation of (R)‐Rolipram Using Chiral Nickel Catalyst. Issue 4 (31st January 2013) - Wen, Lixin; Tang, Feiyu; Ge, Chengsheng; Wang, Xiaodong; Han, Zhi; Wu, Jianyi
Abstract The antidepressant drug (R)‐rolipram (VI) is readily prepared on kilogram scale from isovanillin via a straightforward route.